1990
DOI: 10.1152/ajpgi.1990.258.3.g329
|View full text |Cite
|
Sign up to set email alerts
|

Cold-restraint stress increases rat fecal pellet output and colonic transit

Abstract: Increased fecal pellet output that occurs during cold-restraint stress (CRS) was evaluated systematically. Free-feeding rats, which exhibit a reduced occurrence of gastric ulcers under these conditions, were studied. CRS significantly increased fecal pellet production and fluid content. However, the fecal output produced during CRS was not associated with increased gut secretory activity or somatic motor activity associated with cold restraint and did not occur in anesthetized animals. Cold and restraint stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 0 publications
2
68
1
1
Order By: Relevance
“…Barone et al reported that coldrestraint stress increased fecal output and colonic transit in rats (1). They concluded that increased colonic transit is the major factor involved in defecation induced by cold-restraint stress.…”
Section: Discussionmentioning
confidence: 98%
“…Barone et al reported that coldrestraint stress increased fecal output and colonic transit in rats (1). They concluded that increased colonic transit is the major factor involved in defecation induced by cold-restraint stress.…”
Section: Discussionmentioning
confidence: 98%
“…The number of fecal pellets expelled by each mouse per hour during WAS or during the same period for the control group while in their cages was used as an indirect measure of colonic motility, as previously described (Barone et al, 1990;Monnikes et al, 1993).…”
Section: Fecal Pellet Outputmentioning
confidence: 99%
“…The number of fecal pellets reflects the degree of stress (Barone et al, 1990). Figure 5 shows the number of fecal pellets per hour in SPF WAS mice and SPF control mice.…”
Section: Defecation During Wasmentioning
confidence: 99%
“…In humans and experimental animals, many reports have indicated that stress affects gastric emptying, gastric secretion, intestinal transit, and colonic motility (1,2). In the colon, stress has been reported to stimulate motility via the activation of autonomic neurons, increasing fecal pellet output, or diarrhea (3,4). To evaluate the relationship between stress and lower intestinal or colonic motility, several experimental models such as cage-restraint, wrap-restraint, and water-avoidance stress models have been used (5,6).…”
Section: Introductionmentioning
confidence: 99%